2015
DOI: 10.6060/mhc150247f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4-Nitro- and 4-Aminophenylazacrown Ethers

Abstract: The study is dedicated to finding optimal reaction conditions for the introduction of 4-nitro-and 4-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…It was found that Ca 2+ (FE = 3), and Ba 2+ (FE = 9.4) cations induced the strongest increase in fluorescence, while no optical changes was observed for other metal cations. [ 89 ] A fluorescence increase was also observed for polymer P16‐HG but to a slightly lower degree: Ca 2+ (FE = 2.3) and Ba 2+ (FE = 4.8). The difference in the sensing properties of monomer 16 and the gel was explained by the competition of dimethylcarbamido groups with crown ether for the formation of coordination with cations and coulomb repulsion of positively charged metal cations.…”
Section: Sensors For Cationsmentioning
confidence: 78%
“…It was found that Ca 2+ (FE = 3), and Ba 2+ (FE = 9.4) cations induced the strongest increase in fluorescence, while no optical changes was observed for other metal cations. [ 89 ] A fluorescence increase was also observed for polymer P16‐HG but to a slightly lower degree: Ca 2+ (FE = 2.3) and Ba 2+ (FE = 4.8). The difference in the sensing properties of monomer 16 and the gel was explained by the competition of dimethylcarbamido groups with crown ether for the formation of coordination with cations and coulomb repulsion of positively charged metal cations.…”
Section: Sensors For Cationsmentioning
confidence: 78%